Development Prospects and Recommendations for Improving Methods for Assessing Digital Investment Potential - Karakulov Farkhod Zaypudinovich (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Economic growth represents a fundamental indicator of national development, primarily influenced by macroeconomic variables including inflation rates and banking sector liquidity, which respectively determine price stability and financial intermediation capacity. Specific Background: While previous research has examined inflation and growth relationships independently, the Russian Federation's transition economy provides a unique context for analyzing these dynamics, particularly given its significant financial stability fluctuations between 2000 and 2024. Knowledge Gap: The joint interactive effects of inflation and banking sector liquidity on economic growth remain inadequately explored, especially for transition economies where structural and institutional characteristics differ substantially from developed markets. Aims: This study empirically investigates the relationship between inflation, banking sector liquidity, and GDP growth in the Russian Federation using ordinary least squares regression with robust standard errors and logarithmic transformations applied to annual data from 2000 to 2024. Results: The analysis reveals that inflation exhibits a positive and statistically significant effect on GDP growth (coefficient = 0.507, p = 0.0001 in the log-log-log model with R² = 0.650), while banking sector liquidity demonstrates a weaker, secondary impact requiring cautious interpretation. Novelty: This research uniquely examines inflation and banking liquidity as joint interactive economic phenomena rather than isolated variables, employing comprehensive model comparisons including multiple logarithmic transformation approaches. Implications: These findings suggest that controlled inflation management can stimulate economic activity and sustainable growth, while banking liquidity plays a supportive role, offering valuable guidance for central banks and policymakers in transition economies regarding monetary policy formulation and financial stability management.Keywords : Economic Growth, Inflation, Banking Sector Liquidity, OLS Regression, Russian EconomyHighlight : Inflation demonstrates positive statistical significance on Russian GDP growth (2000-2024 analysis). Banking sector liquidity shows weaker influence requiring cautious interpretation in growth models. Log-Log-Log transformation achieves highest explanatory power with R² of 0.650.